Research of data acquisition instrument based on domestic key chip - Zhao Qian; Luo Tongding; Chen Yanli; Wang Jing; Lv Zongjing; Li Haitao; Zhang Yanxia; Ruan Linbo (Dianzi Jishu Yingyong, 2022)
The high performance data acquisition system is widely used in scientific research such as high energy physics, particle physics experiment and radiation detection, which is the key equipment of many large scientific experiment. The core devices of data acquisition instrument mainly include ADC and FPGA which are monopolized by developed countries for a long time. Especially high-performance ADC and FPGA, which are strictly relevant to China′s technology contractions, so it’s important to research the high performance data acquisition system based on the core devices of the domestic. The paper sketches the embargo on the equipment of core electronic components and key instruments based on the " Wassenaar Arrangement " and the theory of high performance data acquisition system. This paper researches the production status of the domestic high-performance ADC and FPGA, and makes the performance comparison. After that, the present situation of the oscilloscope and the data acquisition instrument are compared. Finally, the paper discusses the substitution of core electronic components.